Variation analysis and comparison of leaf and fruit traits of triploid hybrid progeny in jujube - Xuan, Jiayuan; Ma, Quanhui; Ge, Lixin; Yan, Fenfen; Yu, Jun; Wang, Jiurui; Wu, Cuiyun; Liu, Mengjun (Frontiers in Plant Science, 2025)
IntroductionPolyploid hybrid progeny have both ploidy and hybridization effect, and abound in genetic variation of traits, which is an important material for the breeding of excellent new varieties.Ploidy breeding is an important means to improve and cultivate new varieties, which could overcome distant hybridization incompatibility and play a great significance to species evolution and environmental adaptation.Therefore, triploid breeding has a wide range of application value in germplasm innovation and cultivation of excellent new varieties of fruit trees.MethodsIn order to reveal the trait characteristics and variation analysis of leaves and fruits of triploid hybrids, the ploidy identifications and SSR analysis were carried out through all progeny, and the leaf, stomata, thorn, fruit quality and other traits were compared and analyzed between the triploid and diploid progeny. The genetic variation of the triploid progeny were further analyzed, which could provide reference for hybrid parents selection, offspring traits prediction, ploidy breeding of jujube.ResultsThe results indicated that the triploid progeny exhibited significantly higher values for leaf width, straight thorn length, and stomatal length compared to diploid individuals. However, the leaf shape index and stomatal density were significantly lower in triploids than in diploids. Furthermore, a low genetic trend was observed for leaf traits in triploid progeny, while needle prick traits displayed a high genetic trend. In contrast, stomatal width and stomatal density showed moderate to low genetic trends. Significantly, the single fruit weight, single fruit kernel weight and soluble solids content were significantly higher in triploids compared to diploids. However, the kernel index and titratable acid content were significantly lower in triploids than diploids. The genetic trend showed a high inclination towards single fruit weight, fruit length, fruit shape index, kernel transverse diameter and vitamin C content in triploid offspring. The edible rate exhibited a moderate genetic trend, while kernel longitudinal diameter, kernel index, and titratable acid content displayed a low genetic trend.DiscussionFirst, the occurrence of polypoloid hybrid progeny. Second, triploid hybrid progeny of jujube has typical polypolid traits. Finally, abondance of genetic variations of traits in triploid progeny.